Prevalence and Associated Risk Factors of Intestinal Parasitic Infections in Children at Slum Area of Karachi (Medical Forum Monthly, 2022)
Objective: To determine the prevalence and associated factors for intestinal parasitic infections in children aged 5 to 15 in Khuda Ki Basti, Karachi, Pakistan.Study Design: Cross-sectional studyPlace and Duration of Study: This study was conducted at Community Health Sciences, Hamdard College of Medicine & Dentistry, Hamdard University, Karachi from May, 2018 to August, 2018 for a period of four months.Materials and Methods: Two hundred eight children aged 5 to 15 years were randomly selected after permission from the Institutional ethics review committee. The stool specimens were collected and taken to the laboratory. SPSS version 23.0 was used for data entry and analysis. Frequency and percentages were calculated for description variables.Results: Stool examination was carried out for 208 children. Four intestinal parasites were identified with an overall prevalence of 38 (18.27%). The most prevalent intestinal parasite found was Entamoeba histolytica (10.10%) then Ascaris lumbricoides (03.36%), Giardia lamblia (03.36%) and H. nana (01.44%).Conclusion: The overall prevalence of parasite infections was low in this study due to good hygienic practices, such as a significant number of children wash their hands before eating and a large number of children wash their hands after using the toilet.